Peran Pengetahuan, Sikap, dan Pengawasan Orang Tua dalam Mengatasi Insomnia pada Remaja Akibat Kecanduan Game Online - Embuai, Yowan; Embuai, Selpina; Djurumana, Yohana; Soakakone, Minnalia (KAMBOTI: Jurnal Sosial dan Humaniora, 2025)
This study investigates the relationship between online gaming behavior and the incidence of insomnia among students at SMA Negeri 22 Seram Bagian Barat. The rapid development of technology and internet accessibility has led to the increasing popularity of online games, especially among teenagers. While online gaming can serve as an enjoyable and beneficial pastime, prolonged exposure can lead to addiction, causing negative impacts on physical and mental health, particularly sleep disturbances such as insomnia. This research uses a cross-sectional analytic design with 118 students as participants, and data were collected using questionnaires. The study explores how knowledge, attitudes, and parental involvement influence online gaming behavior and insomnia. Statistical analysis using Chi-Square tests revealed significant relationships between both knowledge and attitudes toward gaming and insomnia, while no significant relationship was found between parental involvement and insomnia. The findings suggest that while students are aware of the negative effects of excessive gaming, their behavior is often influenced by peer interactions, leading to disrupted sleep patterns. It is recommended that schools, parents, and communities collaborate to educate teenagers on managing gaming time and maintaining a healthy sleep routine. This study also highlights the need for further research with a broader sample and the inclusion of other factors, such as social media use and academic stress, to provide a more comprehensive understanding of the factors influencing teenage insomnia.